2004
DOI: 10.1111/j.1527-3458.2004.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology, Clinical Efficacy, and Behavioral Toxicity of Alprazolam: A Review of the Literature

Abstract: Alprazolam is a benzodiazepine derivative that is currently used in the treatment of generalized anxiety, panic attacks with or without agoraphobia, and depression. Alprazolam has a fast onset of symptom relief (within the first week); it is unlikely to produce dependency or abuse. No tolerance to its therapeutic effect has been reported. At discontinuation of alprazolam treatment, withdrawal and rebound symptoms are common. Hence, alprazolam discontinuation must be tapered. An exhaustive review of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 246 publications
(235 reference statements)
5
108
0
16
Order By: Relevance
“…The absence of impairment on other tasks indicates that decisions made on the basis of material remembered over very short (working memory task) or long (learning task) periods of time, or which required ongoing problem solving (the spatial working memory task that required the subjects to learn a complex hidden maze over successive trials) were not affected at the low dose. In a recent review of alprazolam and cognitive function studies it was found that very few comparisons (approx 10%) have yielded cognitive impairment at 0.5 mg doses (Verster and Volkerts, 2004). In the current study, the impairment associated with the higher dose of alprazolam (1 mg) was generalized across all aspects of cognitive function assessed, although the magnitude of impairment did differ between tasks.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The absence of impairment on other tasks indicates that decisions made on the basis of material remembered over very short (working memory task) or long (learning task) periods of time, or which required ongoing problem solving (the spatial working memory task that required the subjects to learn a complex hidden maze over successive trials) were not affected at the low dose. In a recent review of alprazolam and cognitive function studies it was found that very few comparisons (approx 10%) have yielded cognitive impairment at 0.5 mg doses (Verster and Volkerts, 2004). In the current study, the impairment associated with the higher dose of alprazolam (1 mg) was generalized across all aspects of cognitive function assessed, although the magnitude of impairment did differ between tasks.…”
Section: Discussionmentioning
confidence: 97%
“…Alprazolam induces anxiolytic effects by facilitating the binding of GABA to GABAergic receptors. This action occurs non-selectively across brain structures and results in sedation (Verster and Volkerts, 2004). Although many studies have investigated the effects of alprazolam on different cognitive functions, this study is the first to directly compare the effects across a range of cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triazole derivatives also used as potent hypnotic agents. This type of derivatives are fused triazole at 1,2-position of 1,4-benzodiazepines to give Estrazolam(14) [23], Triazolam(15) [24] and Alprazolam(16) [25]. The triazole derivatives also used as anti diabetic [29] like Sitagliptin(17) [26,27], anti HIV agent like Maraviroc (18) [28], anticancer agents [30],antioxident [32] and antibacterial [33].…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal symptoms or rebound symptoms may occur after ceasing treatment abruptly following a few weeks or longer of steady dosing, and may necessitate a gradual dose reduction (10,11).…”
Section: Introductionmentioning
confidence: 99%